ANCIENT KYRGYZ YENISEI WRITING (5th-6th CENTURIES) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article provides a brief summary of the general issues of writing and alphabets, their types, raises the question of the need to consider the Yenisei script as the oldest Kyrgyz script from among the common Turkic written monuments, still known as the Orkhon-Yenisei script. It is also noted that the Kyrgyz people used the Central Asian Chagatai script in Arabic graphics even before the October Revolution.
Keywords: ancient Kyrgyz script, Yenisei script, oral speech, writing, pictographic, ideographic, phonographic, phoneme, alphabet, great power of the Kyrgyz, Kyrgyz Khanate, Chagatai script